2014
DOI: 10.1007/s13277-014-2919-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting prostate cancer cell metabolism: impact of hexokinase and CPT-1 enzymes

Abstract: Glycolysis has been shown to be required for the cell growth and proliferation in several cancer cells. However, prostate cancer cells were accused of using more fatty acid than glucose to meet their bioenergetic demands. The present study was designed to evaluate the involvement of hexokinase and CPT-1 in the cell growth and proliferation of human prostate cancer cell lines, PC3, and LNCaP-FGC-10. Hexokinase and CPT-1 activities were examined in the presence of different concentrations of their inhibitors, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…As noted above, benign prostate cells evade oxidative phosphorylation at baseline. It has been shown that early prostate cancers rely on lipids and other energetic molecules for energy production and not on aerobic respiration (16, 17). Therefore, the Warburg effect does not hold consistent in the pathogenesis of prostate cancer, as these cells do not have the increased glucose uptake (18).…”
Section: Warburg Effect In Prostate Cancermentioning
confidence: 99%
“…As noted above, benign prostate cells evade oxidative phosphorylation at baseline. It has been shown that early prostate cancers rely on lipids and other energetic molecules for energy production and not on aerobic respiration (16, 17). Therefore, the Warburg effect does not hold consistent in the pathogenesis of prostate cancer, as these cells do not have the increased glucose uptake (18).…”
Section: Warburg Effect In Prostate Cancermentioning
confidence: 99%
“…The data of Guo et al (52) suggest substantial decreases in flux through the PPP and glycolytic pathways, which may be consistent with inhibition of hexokinase II but does not prove it since inhibition of these pathways could result from other mechanisms such as acid inhibition of specific enzymes in the PPP and glycolytic pathways. Sadeghi et al (18) have reported the inhibition of hexokinase with 600 μM LND in prostate cancer cells using glucose 6-phosphate dehydrogenase (G6PD)-coupled assay. Cervantes-Madrid et al (17) have also suggested the inhibitory effects of LND on hexokinase based on genetic manipulation of hexokinase mRNA.…”
Section: Other Effects Of Lonidamine (Lnd)mentioning
confidence: 99%
“…34 HKII is also involved in the increase in glucose metabolism after androgen deprivation in PTEN/tumor protein p53-(TP53)-deficient PCa cells. 36 Moreover, pentose phosphate pathway (PPP) is promoted by an AR/mTOR-mediated mechanism, maintaining glucose-6-phosphate dehydrogenase levels higher during PCa progression. 36 Moreover, pentose phosphate pathway (PPP) is promoted by an AR/mTOR-mediated mechanism, maintaining glucose-6-phosphate dehydrogenase levels higher during PCa progression.…”
Section: Curious Case Of Glycolytic Metabolism In Prostatementioning
confidence: 99%